Nutritional And Antioxidant Analysis Of Cookies Made From Sorghum Flour - Aisha, Lathifa Nur; Kurniasih, Nunung (ISTEK, 2024)
One type of snack that is highly favored by the public is desert. Replacing wheat flour with food that can be produced in Indonesia, such as sorghum, can reduce wheat imports. It is expected that sorghum flour will increase the benefits and nutritional value of cookie products. Wheat flour is one of the main ingredients for making cookies. Sorghum has almost the same nutritional content as wheat flour, therefore sorghum can be used as a substitute for wheat flour in food raw materials. The purpose of this study was to determine the nutritional content and antioxidants found in cookies made from sorghum flour. Carbohydrate, protein, and fat values as well as antioxidant activity values for the replaced sorghum flour cookies were measured by gravimetric and titrimetric methods. The results met the standards of SNI No.2973-2011 for carbohydrate, fat, and protein tests.